Ⅰ期肺腺癌VATS肺叶切除与亚肺叶切除预后比较 (Zhongguo Fei Ai Za Zhi, 2017)
BACKGROUND AND OBJECTIVE: National Comprehensive Cancer Network (NCCN) guidelines recommend video-assisted thoracoscopic surgery (VATS) anatomical lobectomy as the first choice for the treatment of resectable lung cancer. However, sublobar resection offers significantly better functional preservation compared with lobectomy for stage Ⅰ lung cancer. At present, the inferiority of sublobar resection to lobectomy is still uncertain. Herein, we compared the prognoses of these two types of surgical treatment for stage Ⅰ lung adenocarcinoma. METHODS: Retrospective research was conducted on 258 patients with stage Ⅰ lung adenocarcinomas who underwent VATS lobectomy and sublobar resection at the First Affiliated Hospital of Guangzhou Medical University between January 2009 and December 2011. VATS lobectomy was performed on 222 patients, and VATS sublobe resection was performed on 36 patients. Propensity score matching analyses were conducted on the two groups. RESULTS: A total of 70 patients were matched in the two groups. No significant difference was observed between the lobectomy and sublobar resection groups after matching (P=0.137). The disease-free survival (DFS) of the two groups were 49.3 and 42.7 months, and their overall survival (OS) were 50.3 and 49.0 months (P=0.122). Further, stratified analysis showed no significant differences in DFS and OS between the two groups with stage Ia lung adenocarcinoma. Nevertheless, the DFS and OS of the two groups significantly differed in matched patients with stage Ib lung adenocarcinomas. CONCLUSION: Sublobar resection could achieve a similar prognosis to VATS lobectomy for stage Ia lung adenocarcinoma. Lobectomy should still be the first choice for the treatment of stage Ib lung adenocarcinoma.